Towards efforts to enhance tax revenue mobilisation in Africa: Exploring synergies between industrialisation and ICTs - Isaac Kwesi Ofori; Pamela E. Ofori; Simplice Asongu (African Governance and Development Institute (AGDI), 2021)
Motivated by the momentous rise in ICT diffusion, the implementation of the African Continental Free Trade Area agreement, and the expected rebound of foreign direct investment inflow to Africa from 2022, this study examines the joint effects of industrialisation and ICT diffusion on resource mobilisation in Africa. To this end, we use data on 42 African countries for the period 1996 - 2020 for the analysis. First, we provide evidence robust to several specifications from the dynamic system GMM to show that although unconditionally both industrialisation and ICT diffusion enhance (i) goods and services tax (GST), and (ii) profits, corporate and income tax (PCIT) mobilisation efforts in Africa, the effects of the former are rather remarkable in the presence of the latter. Particularly, the results show that, while ICTs amplify the effect of industrialisation on GST, only ICT usage and ICT skills matter for PCIT. Second, the study unveils ICT thresholds for complementary policies. Accordingly, industrialisation and ICTs are necessary and sufficient conditions for tax revenue mobilisation only below some ICT thresholds. Above these ICT thresholds, complementary policies are needed to maintain the overall positive incidence on tax revenue mobilisation. Policy recommendations are provided in the end.
Keywords: C33; F6; H2; H71; O33; O55; 330; AfCFTA; Africa; ICT access; ICT diffusion; Industrialisation; Tax; Revenue